Effect of hot water treatment of seeds on seed quality parameters and seedling growth parameters in bell pepper (Capsicum annuum) - SINGH, SURYAPAL; BHARAT, NARENDER K; SINGH, HARSHITA; KUMAR, SUNIL; JAKHAR, SATBIR; VIJAY, VIJAY (The Indian Journal of Agricultural Sciences, 2019)
The experiment was undertaken to extrapolate the effect of hot water seed treatment comprised of different ranges of temperature (47-49, 50-52 and 53-55°C) and different duration of time (30, 45 and 60 min.) on seed quality parameters and seedling growth parameters in bell pepper (Capsicum annuum L.) cv. Solan Bharpur. The aim was to improve seed quality parameters and seedling growth parameters in nursery. Results showed that under in vitro conditions, the hot water treated seed with temperature 50-52 °C for 30 min. showed maximum germination, seedling length, seedling dry weight, seed vigour index-I and seed vigour index-II as compared to untreated seeds (control). In nursery conditions, same treatment, viz. temperature 50-52 °C for 30 min. showed maximum values w.r.t. total emergence, seedling height, seedling dry weight, seed vigour index-I and seed vigour index-II as compared to control.